Analisis Perilaku Pedagang Grosir Pakaian di Pasar Pagi Samarinda dalam Perspektif Etika Bisnis Islam - Mahmudhatul Munawaroh; Muhammad Iswadi; Yusran Yusran (Borneo Islamic Finance and Economics Journal, 2022)
This research is motivated by behavior in trading activities, where trader behavior or trader ethics should be important to pay attention to because along with the times marked by very rapid economic developments, it causes higher business competition. For example, there are still many traders who make deviations in trading, it is done to get multiple profits by ignoring Islamic business ethics. In the Islamic economy, it has explained about the ethics that must be carried out by traders in carrying out buying and selling activities. This study aims to 1) to determine the behavior of clothing wholesalers in the Samarinda Morning market; 2) to know the behavior of clothing wholesalers in the Samarinda Morning market according to the perspective of Islamic business ethics. This type of research is qualitative research using a Descriptive Qualitative approach. The focus of this study is the Behavioral Analysis of Clothing Wholesalers in the Samarinda Morning Market in the Perspective of Islamic Business Ethics. The data sources in this study are Muslim clothing wholesalers, buyers, and UPT Samarinda Morning Market. The data collection techniques used are observation, interviews, and documentation. The data analysis techniques used are techniques developed by Miles and Huberman, namely data collection, data reduction, data presentation, and conclusion drawing/verification. Meanwhile, the data validity techniques used are observation extension techniques, techniques for increasing persistence in research, and triangulation techniques. The results obtained from this study show that, most of the traders in the Samarinda Morning Market are already good in terms of hospitality, quality of goods/products, appointments, service, and competition among traders. Although there are still traders who make deviations in trading. Meanwhile, the behavior of clothing wholesalers in the Samarinda Morning market seen from the five principles of business ethics in Islam, namely the principle of unity (tawhid), the principle of balance (justice), the principle of free will (free will), the principle of responsibility (responsibility), and the principle of benevolence (ihsan) shows that most traders hold the five principles above. Although there are still some traders who do not hold this principle, most traders have made trades in accordance with the principles of Islamic business ethics. Keywords: Merchant Behavior, Islamic Business Ethics